2020
DOI: 10.1155/2020/8874272
|View full text |Cite
|
Sign up to set email alerts
|

DPP4 Activities Are Associated with Osteopenia/Osteoporosis and Fracture Risk in Newly Diagnosed Type 2 Diabetes

Abstract: Background. Recent studies have shown the beneficial effect of dipeptidyl peptidase-4 (DPP4) inhibitor on bone turnover in diabetes mellitus. However, little clinical evidence for DPP4 activity in newly diagnosed type 2 diabetes is available. This study was designed to investigate the relationship between plasma DPP4 activity and osteoporosis/osteopenia and fracture risk in newly diagnosed type 2 diabetes. Methods. A total of 147 subjects with newly diagnosed type 2 diabetes were enrolled for this cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…A human study reported that elevated plasma DPP activities were associated with a higher proportion of osteoporosis/osteopenia in people with newly diagnosed T2D. (90) While not directly linked to DPP-4i use, this finding suggests a potential relationship between DPP activity and bone health in people with T2D. Elevated DPP activity may be an indicator of underlying mechanisms that could influence bone health, warranting further investigation.…”
Section: Human Studiesmentioning
confidence: 96%
“…A human study reported that elevated plasma DPP activities were associated with a higher proportion of osteoporosis/osteopenia in people with newly diagnosed T2D. (90) While not directly linked to DPP-4i use, this finding suggests a potential relationship between DPP activity and bone health in people with T2D. Elevated DPP activity may be an indicator of underlying mechanisms that could influence bone health, warranting further investigation.…”
Section: Human Studiesmentioning
confidence: 96%
“…Furthermore, it has been found that in normoglycemic postmenopausal women, DPP4 activity is associated with an increased risk of osteoporosis, insulin resistance, inflammation and decreased GLP-1 levels [20]. In addition, high plasma DPP4 levels in type II diabetic patients have been linked with bone loss, as well as an increased risk of bone fractures [21].…”
Section: Of 20mentioning
confidence: 99%
“…However, a 13-year follow-up study ( 41 ) of 1,536 community-based elderly adults revealed that there was no significant association between basal DPP4 activity and hip BMD, lumbar spine BMD, or incidence of hip fractures. A cross-sectional study with 147 newly diagnosed T2D showed that elevated sDPP4 activity was positively associated with the risk of osteoporosis/osteopenia and fracture ( 42 ). However, a study ( 43 ) of 204 male Japanese diabetics showed no correlation between DPP4 levels and BMD in the lumbar spine or femoral neck.…”
Section: Scientific Evidence Of the Relationship Between Dpp4 And Bon...mentioning
confidence: 99%